Acute non-atherosclerotic ST-segment elevation myocardial infarction in an adolescent with concurrent hemoglobin H-Constant Spring disease and polycythemia vera - Ekarat Rattarittamrong (2018)
© E. Rattarittamrong et al, 2015 Licensee PAGEPress, Italy. Thrombosis is a major complication of polycythemia vera (PV) and also a well-known complication of thalassemia. We reported a case of non-atherosclerotic ST-segment elevation myocardial infarction (STEMI) in a 17-year-old man with concurrent post-splenectomized hemoglobin H-Constant Spring disease and JAK2 V617F mutation-positive PV. The patient initially presented with extreme thrombocytosis (platelet counts greater than 1,000,000/μL) and three months later developed an acute STEMI. Coronary artery angiography revealed an acute clot in the right coronary artery without atherosclerotic plaque. He was treated with plateletpheresis, hydroxyurea and antiplatelet agents. The platelet count decreased and his symptoms improved. This case represents the importance of early diagnosis, awareness of the increased risk for thrombotic complications, and early treatment of PV in patients who have underlying thalassemia with marked thrombocytosis.